Recent advances in catalytic co-pyrolysis of biomass and plastic waste for the production of petroleum-like hydrocarbons - Ryu, Hae Won; Kim, Do Heui; Jae, Jungho; Lam, Su Shiung; Park, Eun Duck; Park, Young-Kwon (Bioresource technology, 2020)
•Recent advances in catalytic co-pyrolysis are introduced.•Catalytic co-pyrolysis is efficient to upgrade the quality of bio-oil.•Acid catalysts improve deoxygenation and aromatization.•Base catalysts facilitate ketonization, aldol condensation, and hydrogen abstraction.•The challenges and future perspective of catalytic co-pyrolysis is discussed. The global economy is threatened by the depletion of fossil resources and fluctuations in fossil fuel prices, and thus it is necessary to exploit sustainable energy sources. Carbon-neutral fuels including bio-oil obtained from biomass pyrolysis can act as alternatives to fossil fuels. Co-pyrolysis of lignocellulosic biomass and plastic is efficient to upgrade the quality of bio-oil because plastic facilitates deoxygenation. However, catalysts are required to produce bio-oil that is suitable for potential use as transportation fuel. This review presents an overview of recent advances in catalytic co-pyrolysis of biomass and plastic from the perspective of chemistry, catalyst, and feedstock pretreatment. Additionally, this review introduces not only recent research results of acid catalysts for catalytic co-pyrolysis, but also recent approaches that utilize base catalysts. Future research directions are suggested for commercially feasible co-pyrolysis process.